Historical developments in the accountancy profession, financial reporting, and accounting theory - Baker, C. Richard, 1946-; Persson, Martin E. (Studies in the development of accounting thought ;, 2021)
This latest volume of Studies in the Development of Accounting Thought, edited by Martin E. Persson, contains ten manuscripts, seven being previously unpublished, authored by C. Richard Baker during an academic career that spans four decades. Historical Developments in the Accountancy Profession, Financial Reporting, and Accounting Theory is divided into two thematic sections. The first covers developments in accounting thought on financial reporting and the accountancy profession, whereas the second section covers developments related to accounting measurements and theory. The historical examination of the development of accounting thought serves as a unifying theme throughout this edited volume, which attempts to pick up on various understudied threads of academic and professional initiatives over the past several hundred years. The material is of value to anyone interested in the intellectual history of the accounting discipline.